2000
DOI: 10.7863/jum.2000.19.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Dilatation of the biliary tree in children: sonographic diagnosis and its clinical significance.

Abstract: We evaluated sonographically 162 children who met the criteria for biliary tract dilatation in the past 18 years. Of these, 131 patients were diagnosed as having anomalous dilatations of the biliary tree (including 112 with choledochal cysts and 19 with biliary duct dilatation and biliary atresia). Biliary tract dilatations in the other 31 patients were due to secondary causes or normal variants. All cases of intrahepatic biliary tree dilatation and those with both intra‐ and extrabiliary duct dilatations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…In our study average size of CDC was 3.290 cm ± 0.514cm (range 1.6-10cms). It has been suggested that there is a 97% confidence of choledochal cyst when the diameter of the common bile duct is greater than 1 cm, which was comparable to observations drawn from our series [8] .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our study average size of CDC was 3.290 cm ± 0.514cm (range 1.6-10cms). It has been suggested that there is a 97% confidence of choledochal cyst when the diameter of the common bile duct is greater than 1 cm, which was comparable to observations drawn from our series [8] .…”
Section: Discussionsupporting
confidence: 80%
“…Most common presentation of CDC in our series was pain abdomen in 16 (53.33%) cases followed by pain abdomen with jaundice in 7 (23.33%) and incidental finding in 7 (23.33%) cases , similar presentation was reported by. [7] The classical triad of abdominal pain, lump and jaundice is not common in a series of CDC by authors like de Vries et al and Lee et al [6,8]. Twenty (80%) of patients had Type-I CDC and 6 (20%) cases had Type-IV cysts.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 13 excluding cases associated with biliary atresia, the accuracy of diagnosing choledochal cysts in extrahepatic biliary tract dilatation was 71% and 97% using cutoffs of 7 mm and 10 mm as the minimum diameter respectively.…”
Section: Differential Diagnosis Of Biliary Dilatation In Childrenmentioning
confidence: 58%
“…BABC had been reported and had names synonymously as biliary duct dilatation with biliary atresia (BDBA), 13 choledochal cyst associated with extrahepatic biliary atresia (CCBA), 18 and type I cyst of BA.19 A survey by the American Academy of Pediatric Surgery Section found that 13% of patients with cystic dilatation of the CBD had extrahepatic biliary atresia.…”
Section: Differential Diagnosis Of Biliary Dilatation In Childrenmentioning
confidence: 99%
“…However it has limitations in imaging a choledochocele. 12 Magnetic Resonance Cholangiopancreaticogram (MRCP) is the investigation of choice and represents the "gold standard" today. MRCP helps in clearly outline the proximal extent of resection and distally pancreaticobiliary malunion.…”
Section: Investigationsmentioning
confidence: 99%